Simulation of Wireless Grid Computmg - Romli, Abdul Rahman (Universiti Teknologi Petronas, 2006)
For the last decade we have seen that there is an extensive increase in the computer and network area. There is faster hardware and sophisticated software that are been release time to time. Even so there are still problems in the field of science, engineering, and business which cannot dealt effectively with the new era of supercomputers. The objective of this paper is to design and implement the wireless simulation for grid computing architecture. The problem that has been state here is whether it is possible or not to design and implement the wireless grid computing in order to enhance the grid computing utilization. This paper is focus onthe designing and implementing the wireless grid computing architecture that will enhance the performance. This project will have 3 phases which is phase 1 consist of system identification and requirement analysis, phase 2 consist of project design and project development and lastly code and unit testing for phase 3. For this project, it will focus on how the wireless architecture can enhance the grid computing usage in the network management. m